Translation Strategies of Cultural-specific Items in Translating Subtitles Indonesian Documentary “Perempuan Tana Humba” - Halim, Vallen Mutiara; Nitsa, Angelique; Ayuretno, Annisa; Santoso, Wulandari (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Translating Cultural-Specific Items (CSIs) could present numerous challenges for translators because each culture communicates differently. Experts have given some approaches to the issue of translating culturally distinctive objects. The researchers used Aixela's (1996) theory for translation technique and Newmark's (1998) theory for analysis and categorization in relation to CSI. The purpose of this qualitative study is to analyze the translation strategies used for cultural-specific items in the translation of the Indonesian documentary